High-Frequency Cerebellar rTMS Improves the Swallowing Function of Patients with Dysphagia after Brainstem Stroke. (11th August 2022) - Dong, Ling-hui; Pan, Xiaona; Wang, Yuyang; Bai, Guangtao; Han, Chao; Wang, Qiang; Meng, Pingping
Abstract : Objective . To explore the efficacy of high-frequency repetitive transcranial magnetic stimulation (rTMS) of the swallowing motor area of the cerebellum in patients with dysphagia after brainstem stroke. Methods . A total of 36 patients with dysphagia after brainstem stroke were recruited and divided into 3 groups. Before stimulation, single-pulse transcranial magnetic stimulation (TMS) was used to determine the swallowing dominant cerebellar hemisphere and the representation of the mylohyoid muscle. The three groups of patients received bilateral cerebellar sham stimulation, dominant cerebellar rTMS + contralateral sham stimulation, or bilateral cerebellar rTMS. The stimulus plan for each side was 10 Hz, 80% resting movement threshold (rMT), 250 pulses, 1 s per stimulus, and 9 s intervals. Sham rTMS was performed with the coil held at 90° to the scalp. The changes in the motor evoked potential (MEP) amplitude and the clinical swallowing function scales of the patients after stimulation were compared among the three groups. Results . 34 patients were finally included for statistical analysis. The scores of penetration aspiration scale (PAS) and functional dysphagia scale (FDS) of the patients after 2 weeks of rTMS in the unilateral stimulation group and bilateral stimulation group were better than that in the sham stimulation group, and there was no significant difference between the two groups. The increase in the MEP amplitude of the cerebral hemisphere in the bilateral stimulation group was higher than that in the other two groups, and the increase in the MEP amplitude in the unilateral stimulation group was higher than that in sham stimulation group. There was no correlation between the improvement in patients' clinical swallowing function (PAS scores and FDS scores) and the increase in MEP amplitude in either the unilateral stimulation group or the bilateral stimulation group. Conclusion . High-frequency rTMS in the cerebellum can improve swallowing function in PSD patients and increase the excitability of the representation of swallowing in the bilateral cerebral hemispheres. Compared with unilateral cerebellar rTMS, bilateral stimulation increased the excitability of the cerebral swallowing cortex more significantly, but there was no significant difference in clinical swallowing function.